Discovering Students’ Cognitive Perspective on the Use of Cooperative Learning in EFL Classroom - Nida Fauziah; Nita Sari Narulita Dewi; Arini Nurul Hidayati; Fuad Abdullah (Jurnal Pendidikan Bahasa, 2022)
This study aims to explore the students' cognitive perspectives when learning English in the classroom using the cooperative learning method. Cooperative learning is a learning method in which students with different learning abilities are conditioned to work together in a group to achieve the same learning goals. Johnson et al. (2013) added that in cooperative learning students can work together and maximize their learning. The data collection technique used in this study was semi-structured interviews conducted on three students as participants in this study. The data was processed qualitatively using thematic analysis. The findings of this study indicated positive cognitive perception obtained from students' learning experiences, namely, the discovery of partners that become supportive system in learning development and also the improvement of self-accountability in learning English.